The wage effects of offshoring to the East and West: Evidence from Germany - Konstantin Koerner (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2021)
This paper analyzes the labor market effects of offshoring in a high-wage home country and how these effects crucially depend on (1) job complexity and (2) the characteristics of the destination country. It thereby links several sources: rich administrative data on individuals and plants in the German manufacturing sector, information on a job's task bundle, and the evolution of imported inputs from low- or high-wage destinations, which are represented by Eastern and Western Europe, respectively. Offshoring to these origins has opposing effects on German wages with respect to the relative task complexity of jobs: While offshoring to the West puts pressure on the wages of complex jobs and increases the wages of simple jobs, offshoring to the East entails the opposite effect. The overall effect adds up to a 4.2 percent increase in wages for jobs with high complexity, while low-complexity jobs see a 3.9 percent decrease in wages. – – In dieser Arbeit werden die heimischen Lohneffekte von Offshoring untersucht. Dabei wird der Produktionsfaktor Arbeit nach der Komplexität seines Aufgabenspektrums unterschieden und Offshoring je nach Lohnniveau des Ziellandes eingeteilt. Letzteres geschieht am Beispiel Westeuropas für Hochlohnländer und am Beispiel der Visegard-Länder bzw. Osteuropa für Niedriglohnländer. In den Lohnregressionen nach Mincer können so die heterogenen Effekte von Offshoring geschätzt werden. Die dafür notwendigen Daten stammen aus verschiedenen Quellen, wie Input-Output-Tabellen (zu mehreren Ländern), Arbeitsmarktdaten der Bundesagentur für Arbeit sowie Umfragedaten zu den Aufgaben im Job. Die Ergebnisse weisen darauf hin, dass Offshoring nach Westeuropa zu relativen Lohngewinnen für eher wenig komplexe Jobs in Deutschland führt, während der Lohn komplexer Jobs negativ beeinflusst wird. Offshoring nach Osteuropa hingegen hat genau die entgegengesetzten Lohneffekte. Zudem wird in diesem Kapitel gezeigt, dass Offshoring nach Westeuropa zu einer arbeitsintensiveren Produktion und Offshoring nach Osteuropa zu einer kapitalintensiveren Produktion führt.
Keywords: F15; F16; J31; 330; Offshoring; Tasks; Trade; Fragmentation; Wages; Globalization